Experimental Study on the Flexural Performance of Sustainable Composites Utilizing Processed Solar Panel Waste - Ikko Yuswanda; Yi Chieh Wu; Betti Ses Eka Polonia; Dinny Harnany; Muhammad Akhsin Muflikhun (LPPM, Institut Teknologi Sepuluh Nopember, Indonesia, 2026)
The rise in end-of-life photovoltaic (PV) waste necessitates recycling pathways. This study pioneers the utilization of PV waste powder as a filler in Digital Light Processing (DLP) 3D-printed resin composites. Three variations, SN 2 (coarse), SN 4 (medium), and SN 6 (fine) were incorporated into a photopolymer matrix and characterized using SEM-EDX, FTIR, and flexural testing. Results reveal a 73% increase in flexural strength, peaking at 33.11 MPa for the SN 2 composite compared to 19.13 MPa for the neat resin. SEM analysis indicates that the angular silicon-based particles in SN 2 effectively diverted crack propagation and facilitated micro-mechanical interlocking, transforming the fracture mechanism from brittle failure to a toughened, energy-absorbing mode. EDX analysis confirmed high silicon purity in the reinforcing phase, while FTIR verified that the filler interaction remained purely physical, preserving the resin’s chemical stability. The finest SN 6 fraction exhibited reduced performance due to particle agglomeration driven by the highly cohesive nature of the fine powder, which acted as stress concentrators, alongside impurity concentration (Rb/Nb) in the dust. These findings demonstrate that upcycling PV waste into DLP materials offers a sustainable, low-cost solution that significantly enhances mechanical performance without requiring complex chemical modification, provided that the particle size is carefully optimized to balance dispersion and interfacial bonding.